Methods for deriving the law of radioactive decay and the law of radiation absorption using the property of the exponent function when studying Physics in the system of secondary vocational education - D. B. Siyukhova; T. I. Demina (Вестник Майкопского государственного технологического университета)
In accordance with the educational standards of the Federal State Educational Standard for Secondary Professional Education, it is intended to familiarize students of professional educational organizations with the properties of radioactive radiation, their practical applications, as well as with some concepts of dosimetry and protection from such radiation.The relevance of this research can be debated for a very long time. But in light of recent events it is obvious.A thorough mastery of all this material is impossible without studying the law of radioactive decay and the law of absorption of radiation.The research problem: the law of radioactive decay and the law of absorption of radiation are expressed using the exponential function N=N_0 e^(-λt) and i=Ie^(-μχ) and are usually not presented in the course of Physics in secondary specialized educational institutions. At best, an appropriate schedule is drawn, but without justification. It seems that this is caused by two reasons: firstly, when writing the exponent function, the base of natural logarithms is used – the number e, which is unknown to intermediate students; secondly, the above laws are usually derived by solving differential equations, which is far beyond the scope of the mathematics curriculum. Meanwhile, both of these difficulties can be easily overcome by using the properties of the exponential function known to students of secondary vocational education.The purpose of the research is to develop a methodology for deriving the law of radioactive decay and the law of radiation absorption, using the properties of the exponential function; to conduct a pedagogical experiment in order to identify the problem of students’ mastery of the proposed material.The research methods used are theoretical justification; calculation; comparison of quantities; graphical analysis of experimental data; generalization of the experimental factors of the study and their explanation.The research results: a methodology has been developed for deriving the law of radioactive decay and the law of radiation absorption using the property of the exponential function; the result of the pedagogical experiment confirmed the effectiveness of the developed methodology.Key conclusions: from the proposed article we can conclude that the presented method for deriving the law of radioactive decay and the law of absorption of radiation using the property of the exponent function can be used by teachers when studying the section «Radioactive Radiation» for both students of professional educational organizations and school students (advanced level).